Pengaruh Program Latihan Drill Like Game Situation Terhadap Pukulan Forehand dan Backhand Pada Olahraga Pickleball - Lestari, Sekar Putri; Kahri, Ma’ruful; Haffyandi, Recky Ahmad (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
One of the increasingly popular sports is Pickleball, which offers a combination of tennis, badminton and table tennis. Pickleball emphasizes control, accuracy, and good reflexes, while still being easy to learn and play for beginners to experienced players. Mastery of basic techniques, including forehand and backhand shots, is essential in playing Pickleball effectively. The drill method, with simulated game situations similar to actual matches, is an effective approach to improve players' skills in this sport. This study aims to determine the effect of the Drill Like Game Situation Training program on Forehand and Backhand shots in Pickleball. The motede of this research is an experiment with a quantitative approach. The population of this study were members of the JPOK pickleball club. The sampling technique used was purposive sampling and obtained a sample of 18 people. The results showed that the Drill Like Game Training Program has a significant effect on forehand and backhand shots in the Pickleball game because this program provides structured and repetitive training, which allows players to improve technique and reliability in performing both shots. The Drill Like Game Training Program also not only improves the technical skills of forehand and backhand shots, but also helps players hone their mental and tactical abilities in the game of Pickleball.